CORRELATION OF EMPLOYMENT STATUS, MOTIVATION AND ACHIEVEMENT IN LEARNING - FIKRIANI AMINUN OMOLU (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2017)
Fulltime students have more free time than working students. They can spare a lot of time on doing tasks from their lecturers and spend the rest to play or to do any other activity they like. While working students must share their time wisely to make a balance of studying and working. The hardship of balancing these two states in some ways, affects students’ achievement in class. To get better achievement, there are many influencing factors. One of them is motivation. Coming across this situation, it becomes an interesting matter to find out correlation of students’ employment status and achievement, students’ motivation and achievement, and correlation of students’ employment status and motivation simultaneously on achievement. Keywords: Correlation, Employment Status, Motivation, Achievement.